1990
DOI: 10.1177/107110079001100108
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Ankle Sprains in Soccer

Abstract: This study investigated the relationship between exposure time and ankle sprains in soccer. Forty-one teams (639 players) from four male senior soccer divisions at different levels of skill (divisions I-VI) were followed prospectively for 1 year. The exposure to soccer and the number of injuries per player were higher in higher divisions, but the injury incidence, percentage of ankle injuries and incidence of ankle injuries were the same at different levels of skill. Of all injuries 17 to 20% were ankle sprain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
162
5
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(194 citation statements)
references
References 13 publications
15
162
5
9
Order By: Relevance
“…Estos resultados corroboran lo dicho en otros estudios 12,13 donde la frecuencia de lesión disminuye de forma progresiva a lo largo de la temporada y donde el número de lesiones aumenta conforme aumenta la carga, principalmente en las primeras semanas de entrenamiento cuando el deportista todavía no se ha adaptado a los entrenamientos En la TA existe un repunte en el mes de abril al volver a aumentar el volumen con el objetivo de preparar la fase de play-off. Como ocurre en otros estudios 15 que no encontraron tendencia clara al obtener dos picos de mayor frecuencia en los meses de marzo y mayo, debido a la necesidad de alcanzar los objetivos de la temporada, lo que genera en los jugadores un mayor stress y fatiga a todos los niveles, lo que muchos autores señalan como factor de riesgo extrínseco importante a tener en cuenta 16,18,19,[35][36][37][38] . A niveles más altos de ansiedad se incrementa el riesgo de lesionarse 39 .…”
Section: Volumen De Ambas Temporadas (E/h)unclassified
“…Estos resultados corroboran lo dicho en otros estudios 12,13 donde la frecuencia de lesión disminuye de forma progresiva a lo largo de la temporada y donde el número de lesiones aumenta conforme aumenta la carga, principalmente en las primeras semanas de entrenamiento cuando el deportista todavía no se ha adaptado a los entrenamientos En la TA existe un repunte en el mes de abril al volver a aumentar el volumen con el objetivo de preparar la fase de play-off. Como ocurre en otros estudios 15 que no encontraron tendencia clara al obtener dos picos de mayor frecuencia en los meses de marzo y mayo, debido a la necesidad de alcanzar los objetivos de la temporada, lo que genera en los jugadores un mayor stress y fatiga a todos los niveles, lo que muchos autores señalan como factor de riesgo extrínseco importante a tener en cuenta 16,18,19,[35][36][37][38] . A niveles más altos de ansiedad se incrementa el riesgo de lesionarse 39 .…”
Section: Volumen De Ambas Temporadas (E/h)unclassified
“…Studies regarding the skill levels show partly contradictory results. Ekstrand & Tropp (5) and Nielsen & Yde (19), have reported that high-level players have a higher incidence of injury in games, but a lower incidence in training sessions than low-level players. Inklaar et al (12), found that high-level teams have a significantly higher risk of injury than teams at a lower level of play.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we believed that the lack of di erence between groups might be related to the characteristic of the single-leg test used. Ankle sprains are associated to fast movements, such as jumps, sprints and changes in direction 2,[4][5][6]8 ; however, the measures used herein, stabilization time and COP reposition in the support, are more accurate to di erentiate between individuals with and without stability 35,37 .…”
Section: Discussionmentioning
confidence: 93%
“…e ankle sprains are very common in soccer due to the demand of changes in direction performed with high velocities, after jumps and during the sprints itself 2,4,6 . ese rapid changes in direction or landing on irregular surfaces produces a large supination torque, causing the ankle to perform an excessive movement, overloading the joint and its structures, mainly the anterior talo-bular and the calcaneo-bular ligaments 7 .…”
mentioning
confidence: 99%